2018
DOI: 10.1002/cam4.1674
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of CD5 and CD43 predicts worse prognosis in diffuse large B‐cell lymphoma

Abstract: Both CD5 and CD43 are expressed on the surface of B lymphocytes of definite phase and associated with the adverse outcome in diffuse large B‐cell lymphoma (DLBCL). However, the relationship between CD5 and CD43 expression and the prognostic value of CD5/CD43 coexpression in DLBCL are unknown. We herein determined the correlation between CD5 and CD43 expression, as separate factors or in combination, with the clinicopathological features and survival of 200 patients with DLBCL receiving standard chemotherapy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…Chien et al examined CLA expression in almost 90 AML patient samples from the peripheral blood and the BM and found a 4-fold higher expression for relapsed/refractory patients than for newly diagnosed AML patients [ 17 ]. These results were in line with increased CLA expression in cancerous plasma cells from relapsed/refractory patients compared to newly diagnosed MM patients [ 15 , 47 , 48 ]. Moreover, it was shown that CLA was increased in hypoxic MM cells, indicating the progression of MM to more advanced stages.…”
Section: The Role Of E-selectin In Cancer Pathophysiologysupporting
confidence: 69%
“…Chien et al examined CLA expression in almost 90 AML patient samples from the peripheral blood and the BM and found a 4-fold higher expression for relapsed/refractory patients than for newly diagnosed AML patients [ 17 ]. These results were in line with increased CLA expression in cancerous plasma cells from relapsed/refractory patients compared to newly diagnosed MM patients [ 15 , 47 , 48 ]. Moreover, it was shown that CLA was increased in hypoxic MM cells, indicating the progression of MM to more advanced stages.…”
Section: The Role Of E-selectin In Cancer Pathophysiologysupporting
confidence: 69%
“…Moreover, some promising targets have been detected for the prevention and treatment of relapsed/refractory DLBCL [ 8 ]. For instance, coexpression of CD5 and CD43 may predict a poor prognosis of DLBCL patients [ 9 ]. A high NEAT1_1 level is positively correlated with stage, IPI, extranodal involvement, drug response, and poor prognosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…B-1 cells are somewhat resistant to rituximab, and this has implications for treatment outcome because B-1 cells have immune regulatory properties. 28,29 The resistance to B-1 cells to rituximab has also been seen in mice. 30 These B-1 cells are almost always negative for CD24 and thus distinct from the memory B cells.…”
Section: Discussionmentioning
confidence: 98%